The Determination of Laser Spot Size of an Optical Tweezers by Stuck Bead Method - Mat Yeng, Muhamad Safuan; Ayop, Shahrul Kadri; Hamid, Muhammad Yunus (Journal of Science and Technology, 2017)
The determination of laser spot size is one of an essential requirement in a laser system. This study proposed an alternative method to determine the laser spot size by using stuck bead method (SBM). 3 Âµm polystyrene bead stuck at glass slide was used to scan laser spot in an optical tweezers setup. This was compared with beam waist measurement using Knife Edge Method. In both methods, quadrant photo-diode (QPD) was used to collected position dependent intensity profiles at three applied laser powers (95 mW, 122 mW and 150 mW) of 915 nm wavelength. Even though there is still no standard definition of beam waist, the Â using SBM is suggested as the alternative definition of beam spot in optical tweezers application.